Perceptions of undergraduate graphic design students on the educational potential of facebook - Souleles, Nicos (My University, 2012)
The popularity of Facebook among university students inevitably raises questions on the educational potential of this Social Networking Site for Higher Education. From the limited literature on the instructional uses of Facebook, one can draw conflicting conclusions. Benefits were identified through the communicative potential, student participation in study groups and through informal learning, i.e. learning that takes place outside the formal structures of the learning environment. In contrast, it is also argued that the instructional benefits of Facebook are not straightforward. This phenomenographic investigation examines the perceptions of undergraduate Graphic Design students in a higher education institution in Cyprus, on the use of Facebook for teaching and learning. Characteristic of Art and Design education is the centrality of the studio and student self-reflection. Despite some literature that considers Facebook provides a viable alternative to the physical studio, the participants in this investigation expressed a preference for face-to-face instruction and consider Facebook as complimenting rather than replacing studio practices. Some participants benefited from the use of Facebook by joining support groups and exploring information relevant to their studies. Further research can investigate how Facebook can be embedded in studio-based teaching and learning.
Keywords: Facebook (Electronic resource); Graphic design; Non-formal education